The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2015
DOI: 10.1002/cpt.155
|View full text |Cite
|
Sign up to set email alerts
|

Physiologically based and population PK modeling in optimizing drug development: A predict–learn–confirm analysis

Abstract: Physiologically based pharmacokinetic (PBPK) modeling and classical population pharmacokinetic (PK) model‐based simulations are increasingly used to answer various drug development questions. In this study, we propose a methodology to optimize the development of drugs, primarily cleared by the kidney, using model‐based approaches to determine the need for a dedicated renal impairment (RI) study. First, the impact of RI on drug exposure is simulated via PBPK modeling and then confirmed using classical populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 18 publications
(31 reference statements)
0
11
0
Order By: Relevance
“…Generally, PK profiles of drugs are expected to differ in cancer populations compared with profiles in healthy subjects. In many cases, clearance of anti-cancer drugs decreases in cancer patients compared with healthy individuals (Piotrovsky et al, 1998;Houk et al, 2009;Hudachek et al, 2010) for various reasons, including co-morbidities, such as hepatic and renal impairment in cancer patients (Suri et al, 2015). Another possible reason may be changes in MPPGL or CPPGL and differences in the expression of enzymes and transporters (Gao et al, 2016;Billington et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Generally, PK profiles of drugs are expected to differ in cancer populations compared with profiles in healthy subjects. In many cases, clearance of anti-cancer drugs decreases in cancer patients compared with healthy individuals (Piotrovsky et al, 1998;Houk et al, 2009;Hudachek et al, 2010) for various reasons, including co-morbidities, such as hepatic and renal impairment in cancer patients (Suri et al, 2015). Another possible reason may be changes in MPPGL or CPPGL and differences in the expression of enzymes and transporters (Gao et al, 2016;Billington et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The mechanistic nature of PBPK models permits integration of data from in vitro and in vivo studies and can interpolate between organisms (eg, animals to humans) as well as developmental stages (eg, adults to pediatrics). Such PBPK models can complement population PK modeling and simulation and facilitate implementation of a predict‐learn‐confirm approach in drug development . Johnson et al evaluated prediction of CL for 11 drugs, including gentamicin and vancomycin, in neonates, infants, and children with normal kidney and hepatic function and concluded that renal CL of gentamicin was underpredicted in children <5 years of age, whereas the prediction for vancomycin was reasonable .…”
Section: Discussionmentioning
confidence: 99%
“…This case illustrates how PBPK modeling can inform appropriate dosing of renal impairment (RI) patients in phase I/III studies and thereby enable characterization of safety and efficacy in the RI patients during the late stage of drug development 17 . Data from human ADME study revealed that orteronel (see last example) is a drug that is primarily cleared by kidney excretion.…”
Section: Dose Guidance For Renal Impairment Patients a Case Studymentioning
confidence: 99%